Effects of Yoga Therapy on Psychological and Gene Expression States of Healthy Subjects - Sayaka Higuchi; Yukiko Kezuka; Shohei Mitani (Tokyo Women's Medical University Journal)
Background: Yoga is one of the most popular activities for improving health worldwide. However, the investigation of scientific evidence has only just begun. Methods: This study investigated the effects of yoga using two psychological tests, the State-Trait Anxiety Inventory (STAI) and the Profile of Mood States (POMS), and gene expression analysis using quantitative real-time polymerase chain reaction (qPCR). Seven healthy individuals volunteered to participate in the yoga therapy program designed for this study. The participants' saliva was collected for gene expression analyses in a noninvasive manner. Results: No adverse events were observed. The participants were categorized by stress levels (low, normal, or high) based on their psychological tests before the intervention. Participants with normal stress levels experienced the most effective changes in their health, including decreased expression of an inflammatory gene or increased expression of anti-inflammatory genes, after three months of yoga intervention. Those with low and high stress levels retained their initial physical conditions. Conclusions: By using both psychological research and gene expression analysis in the same participants, our study revealed that yoga therapy has the potential to improve both psychological and physical health, especially among those with normal stress levels, with little physical discomfort. These effects should be carefully considered in future large-scale, long-term studies.